Acute Variceal Bleeding: Does Octreotide Improve Outcomes in Patients with Different Functional Hepatic Reserve? - Monreal Robles, Roberto; Cortez Hernández, Carlos Alejandro; González González, José Alberto; Abraldes, Juan G.; Bosques Padilla, Francisco Javier; Silva Ramos, Héctor Noé Guadalupe; García Flores, Jorge A.; Maldonado Garza, Héctor Jesús (2018)
Background. Current guidelines do not differentiate in the utilization of vasoactive drugs in patients with cirrhosis and acute variceal bleeding (AVB) depending on liver disease severity. Material and methods. In this retrospective study, clinical outcomes in 100 patients receiving octreotide plus endoscopic therapy (ET) and 216 patients with ET alone were compared in terms of failure to control bleeding, in-hospital mortality, and transfusion requirements stratifying the results according to liver disease severity by Child-Pugh (CP) score and MELD. Results. In patients with CP-A or those with MELD < 10 octreotide was not associated with a better outcome compared to ET alone in terms of hospital mortality (CP-A: 0.0 vs. 0.0%; MELD < 10: 0.0 vs. 2.9%, p = 1.00), failure to control bleeding (CP-A: 8.7 vs. 3.7%, p = 0.58; MELD < 10: 5.3 vs. 4.3%, p = 1.00) and need for transfusion (CP-A: 39.1 vs. 61.1%, p = 0.09; MELD < 10: 63.2 vs. 62.9%, p = 1.00). Those with severe liver dysfunction in the octreotide group showed better outcomes compared to the non-octreotide group in terms of hospital mortality (CP-B/C: 3.9 vs. 13.0%, p = 0.04; MELD